Data privacy: A discussion in light of Information Science paradigms - Brandao Pessoa, Luiz Gustavo de Sena; Ferreira de Sousa, Marckson Roberto (Advanced Notes in Information Science, 2022)
Data privacy has been gaining more and more space in the academic and professional environment. In this sense, Information Science (IS) can contribute to this field of study, as the properties of information combined with available technologies are part of its scientific approaches. Based on the reflection on the Theory of Concentric Spheres (TCS), this article sought to reflect in the light on Information Science aspects related to paradigms and terminological issues that permeate the theme of data privacy. The research is exploratory and descriptive. During the investigation, we sought to know the different terminological currents that deal with privacy to relate to the theory above, verifying whether or not there is a relationship in its application with the paradigms of Information Science. It is concluded that part of the doctrine understands that the concept of privacy is generalized. Another part diverges, stating that they are different concepts. When comparing TCS with the paradigms of IS, analogous applications between both treated concepts are concluded.